What s in a neem - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Efficacy and Commercialization of Neem Products Edited by A K Brimah, WOELI Publishing services with Goethe Institute, Accra, Ghana, 2000. 78 pp. ISBN 9964978715 GBP 10.95 Euro 18.30